Range of motion in the talo-navicular and the calcaneo-cuboid joints evaluated by ultrasound during clubfoot treatment with normal references up to the age of four years - Johansson, A. (J Child Orthop, 2018)
PURPOSE: Previous ultrasound studies of clubfeet have mainly focused on the first year of life. The purpose of this study was to improve the evaluation of the talo-navicular and calcaneo-cuboid joints by adding new variables, evaluating the repeatability of ultrasound measurements for normal feet and clubfeet and establishing values for normal feet up to four years of age. METHODS: A control group of 105 children divided into ten age groups, and 71 clubfeet in 46 children were examined. Four new variables were introduced: medial malleolus–Talar head–Navicular distance, medial tangent of the talus to the medial border of the navicular distance, the angle between the longitudinal axis of the talus and a line from the centre of the talar head to the medial corner of the navicular, the angle between the lateral borders of the calcaneus and the cuboid. The mobility in the talo-navicular and the calcaneo-cuboid joints was assessed by comparing measurements with the foot in adduction and abduction. RESULTS: The variables could be assessed with fair to very good intra- and inter-observer repeatability (intraclass correlation coefficient > 0.8 and ≥ 0.6, respectively), with a few exceptions. There was less movement in talo-navicular and calcaneo-cuboid joints in clubfeet than in controls. CONCLUSION: Morphology of normal feet and clubfeet, as well as mobility in the talo-navicular and calcaneo-cuboid joints, can be assessed by ultrasound with a fair to very good reliability from birth to the age of four years. LEVEL OF EVIDENCE: III